2010
DOI: 10.1080/10986061003689618
|View full text |Cite
|
Sign up to set email alerts
|

A Local Instruction Theory for the Development of Number Sense

Abstract: Gravemeijer's (1999Gravemeijer's ( , 2004 construct of a local instruction theory suggests a means of offering teachers a framework of reference for designing and engaging students in a set of sequenced, exemplary instructional activities that support students' mathematical development for a focused concept. In this paper we offer a local instruction theory to guide the design of a set of instructional activities in support of the development of number sense. We make explicit the goals, assumptions, underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 44 publications
0
21
0
2
Order By: Relevance
“…A local instruction theory (LIT) consists of ''the description of, and rationale for, the envisioned learning route as it relates to a set of instructional activities for a specific topic'' (Gravemeijer 2004, p. 107). In a previous article, we describe our LIT for the development of number sense with a focus on whole-number mental computation (Nickerson and Whitacre 2010). Broadly, the envisioned learning route involves students moving from dependence on standard algorithms to reasoning flexibly about numbers and operations.…”
Section: Local Instruction Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…A local instruction theory (LIT) consists of ''the description of, and rationale for, the envisioned learning route as it relates to a set of instructional activities for a specific topic'' (Gravemeijer 2004, p. 107). In a previous article, we describe our LIT for the development of number sense with a focus on whole-number mental computation (Nickerson and Whitacre 2010). Broadly, the envisioned learning route involves students moving from dependence on standard algorithms to reasoning flexibly about numbers and operations.…”
Section: Local Instruction Theorymentioning
confidence: 99%
“…Broadly, the envisioned learning route involves students moving from dependence on standard algorithms to reasoning flexibly about numbers and operations. More specifically, our LIT is organized around three goals: (1) students capitalize on opportunities to use number-sensible strategies for problem-solving situations both inside and outside the classroom; (2) students draw on deep, connected knowledge of number and operations to develop a repertoire of number-sensible strategies; and (3) students reason with models to build on their understanding and flexibly use numbersensible strategies (Nickerson and Whitacre 2010). The envisioned learning route is one in which students move from relying on standard algorithms to developing and using their own nonstandard strategies.…”
Section: Local Instruction Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In a next research step, these cognitive characteristics should be reconciled with principles from both domain-general (Van Merriënboer & Kirschner, 2007) and domain-specific (Nickerson & Whitacre, 2010) theories of instructional design. The effectiveness of these environments should be evaluated in various phases of empirical research (Sloane, 2008), using appropriate scientific methods, such as smallscale intervention studies followed by larger randomized controlled trials, before they can be applied in the classroom.…”
Section: From Cognitive Neuroscience To Mathematics Educationmentioning
confidence: 98%
“…It has been found that although teacher candidates' tendencies to standard computational techniques continue after training, number sense can be improved with proper training (Kaminski, 2002;Markovits & Sowder, 1994). Moreover, the research reports that a significant improvement in the number sense of teacher candidates was observed when they attend the courses that focus on the development of number sense (Nickerson & Whitacre, 2010;Whitacre, 2007;Whitacre & Nickerson, 2006).…”
Section: Related Researchmentioning
confidence: 99%